1996
DOI: 10.1109/100.556479
|View full text |Cite
|
Sign up to set email alerts
|

The autonomous mobile robot AURORA for greenhouse operation

Abstract: AURORA has been conceived in order to substitute hard and unhealthy human work inside greenhouses by means of an autonomous mobile robot outfitted with appropriate sensors and operation devices. Emphasis has been put in the development of a new robotic platform specifically designed for greenhouse tasks, governed by a control architecture that supports both autonomous navigation and shared human control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(39 citation statements)
references
References 3 publications
(2 reference statements)
0
38
0
1
Order By: Relevance
“…In the literature, there are two main approaches: mobile robots and human-driven vehicles. An autonomous robot was reported in Mandow et al (1996), where the objective was to demonstrate the autonomous navigation capabilities of the robot in a greenhouse using a constantpressure spraying system. In Adams et al (2003), an inductive guidance system was developed for spraying at constant pressure.…”
Section: Spraying Systemmentioning
confidence: 99%
“…In the literature, there are two main approaches: mobile robots and human-driven vehicles. An autonomous robot was reported in Mandow et al (1996), where the objective was to demonstrate the autonomous navigation capabilities of the robot in a greenhouse using a constantpressure spraying system. In Adams et al (2003), an inductive guidance system was developed for spraying at constant pressure.…”
Section: Spraying Systemmentioning
confidence: 99%
“…An effective system for treating crops in greenhouses should satisfy the following requirements (Naoki et al, 1995) (Mandow et al, 1996) (Acaccia et al, 1998) (Tian et al, 1999) (Nuyttens et al, 2003) (Singh et al, 2005) (Solanelles et al, 2006) (Piccarolo, 2008).…”
Section: Requirements For the New Greenhouse Pesticide Spraying Systemmentioning
confidence: 99%
“…Mandow, et al [14] used pulse-echo ultrasonic sensing to navigate along rows of plants in a green house. Nabout et al [15] found that plants have many different complex forms that cannot be described using simple geometric models.…”
Section: Perception Of Plantsmentioning
confidence: 99%